THE IMPLEMENTATION OF PROBLEM POSING APPROACH THROUGH SENDING QUESTION IN MATHEMATICS LEARNING AT GRADE VIII OF SMP NEGERI 25 PADANG IN YEAR OF RESEARCH 2009/2010 - Deswita, Hera (Universitas Pasir Pengaraian, 2014)
Mathematics learning not only requires an understanding of existing concepts,but also requires training and meaningful learning experiences. However, in the reality, most of students have not been successful in learning mathematics due to the students lack of trained in solving the mathematical problems that found on the books and that given by the teacher. To overcome this problem needs to be improvement in mathematics teaching and learning approaches in schools through a research